Pregnancy outcomes in simultaneous pancreas and kidney transplant recipients: a national French survey study. (15th June 2017) - Normand, Gabrielle; Brunner, Flora; Badet, Lionel; Buron, Fanny; Catton, Marielle; Massardier, Jérôme; Esposito, Laure; Grimbert, Philippe; Mourad, Georges; Serre, Jean E.; Caillard, Sophie; Karam, Georges; et al.
Summary: Simultaneous pancreas and kidney transplantation (SPK) is currently the best therapeutic option for patients with type 1 diabetes and terminal renal failure. Renal transplantation restores fertility enabling women to pursue pregnancies. However, scarcity of available data on pregnancy outcomes in SPK impedes fair medical counseling. Medical files of all pregnancies that lasted ≥3 months among recipients of functional SPK performed between 1990 and 2015 in France were retrospectively analyzed. Twenty‐six pregnancies in 22 SPK recipients were identified. Main maternal complications included gestational hypertension (53.8%) and infections (50%). Cesarean section was performed in 73% of cases. Overall fetal survival was 92.6% with a mean gestational age of 34.2 ± 3 weeks. Four children (16.7% of live births) had a birth weight <10th percentile. Endocrine pancreas graft function remained stable during pregnancy. An acute kidney rejection occurred in two patients, one of which resulting in graft loss. Kidney and pancreas graft survival was, respectively, 96% and 100% at 1 year postconception and did not differ from controls. Pregnancy in SPK is feasible, but patients should be informed of the risks for the fetus, the mother, and the grafts. Planning of pregnancy in SPK women is key to allow a personalized multidisciplinary monitoring, which represents the most straightforward approach to optimize outcomes.